Wheat landraces as sources of high grain quality and nutritional properties - V. P. Shamanin; I. V. Pototskaya; S. A. Esse; M. S. Gladkih; S. S. Shepelev; E. V. Zuev; N. A. Vinichenko; H. Koksel; A. I. Morgounov (Труды по прикладной ботанике, генетике и селекции)
Background. Improving the grain quality of modern spring bread wheat cultivars is a highly relevant task of breeding. To solve this problem, old and local wheat varieties (landraces) are of considerable interest. A rich collection of them is available among the plant genetic resources preserved at VIR. With this in view, the aim of this research was to identify sources of high protein, gluten, macro- and micronutrient content out of the landraces from the VIR collection for improvement of wheat grain quality through breeding.Materials and methods. Field and laboratory research were conducted in the experimental field of Omsk State Agrarian University under the conditions of the southern forest-steppe of Western Siberia in 2020–2021. Sowing was carried out on fallow on conventional sowing dates. Mineral composition in the grain of the studied landraces was analyzed at the Kurchatov Genomic Center, Novosibirsk, using atomic absorption spectrometry techniques.Results. The research results showed that landraces from different regions of Russia, Kazakhstan, Tajikistan, and Kyrgyzstan were characterized by high levels of protein (18.4–18.8%) and gluten (35.9–36.0%) in grain. Landraces from Kazakhstan had low Zn content (on average 38.3 mg/kg), while those from Kyrgyzstan, on the contrary, had high content of Zn (41.9 mg/kg) and Fe (55.1 mg/kg), and landraces from Tajikistan had high K content (3820 mg/kg). A positive relationship between the concentrations of Mg, Mn, Fe, and Zn was found in the grain of wheat landraces.Conclusion. Wheat landraces are of interest as genetic resources for the development of high-protein cultivars with improved nutritional value of grain for the milling and breadmaking industries.